(untitled) (Italian Review of Legal History, 2022)
The Christ Pantocrator taken as an iconographic model to represent the sovereignty in the Regnum Siciliae in the Norman-Swabian age, gave way in the Angevin age to the paupertas which, as a result of the Franciscan preaching welcomed by the Neapolitan sovereigns, became an unavoidable element of legitimacy of the royal power. In a letter written by the Franciscan friar Angelo Clareno to Filippo di Majorca, brother of Queen Sancha of Naples, the characters of the Christiform sovereign are outlined, who exercises power as administrator of the Kingdom, whose sole owner is Christ: a Deo coronato it is only the sovereign who makes himself poor, stripping himself of all desire for power and will to dominate and using public wealth for the sole purpose of providing for the needs of his subjects. The Franciscan novitas centered on the precept of sine proprio codified in the Rule of Francis of Assisi, changed the representation and perspectives of sovereignty, introducing juridical concepts into the public law of the Kingdom intended to broaden the range of meanings of proprietas and dominium. With a retrospective look and in continuity with the tradition of the Kingdom, the last king of the Two Sicilies, Francis II of Bourbon, appealed to the ancient rights of the throne of Roger and Charles III to defend the legitimate sovereignty of the Two Sicilies, thus recalling the image of the sovereign crowned by Godw hose political conduct could only be inspired by the model of christiformitas: a perspective of sovereignty that would soon be overwhelmed by the revolutionary events taking place throughout Europe, of which however it could provide an unprecedented interpretation, proposing itself as a moment of reflection on the Italian and European history of the last two centuries.